Operation Condor: clandestine inter-American system - McSherry, J. Patrice (Social justice, 1999)
Part of a special issue on state terrorism and impunity in Latin America. The writer discusses Operation Condor, a shadowy Latin American military network that represented a striking new level of coordinated repression among the anticommunist militaries in the region—Chile, Argentina, Uruguay, Bolivia, Paraguay, and Brazil. He demonstrates that Condor was a parastatal system that employed criminal methods to eliminate “subversion” and, at the same time, avoided constitutional institutions, ignored due process, and breached all manner of human rights. He analyzes the scanty literature on Condor and on state terrorism to place the discussion in a theoretical context. In addition, he reviews Condor's structures and operations and briefly compares them with the “stay-behind” projects in Europe, secret programs designed by the West for guerrilla warfare and covert operations aimed to undermine Communist and leftist advances. Furthermore, he reflects on the ideologies and doctrines that resulted in Condor and the question of ends and means.